DEVELOPING COLLABORATIVE PROBLEM SOLVING IN PHYSICS OF MATHAYOMSUKSA 5 STUDENTS BY USING PROBLEM – BASED LEARNING - Sitha, Siriwan; Charoen-In, Urit (Journal of MCU Nakhondhat, 2020)
This research is an action research. The objective is to develop the collaborative problem solving in physics of mathayomsuksa 5 students to pass the middle level criteria of PISA 2015's collaborative problem solving assessment framework, by using problem–based learning. The targets are 6 students which were purposive sampling. The instruments used in this research consist of 1) 9 lesson plans using problem – based learning on the topic of sound, take 12 hours, 2) observation form in students’ collaborative problem solving, and 3) assessment forms in students’ collaborative problem solving. It is characterized by a situation related to sound in physics and contains 12 questions, according to PISA 2015's collaborative problem solving assessment framework. The process of this research followed the concept of Kemmis & McTaggart’s action research, include 3 loops. There are 4 steps in the cycle; planning, action, observation, and reflection. Observation form in students’ collaborative problem solving is used While students were learning. And assessment forms in students’ collaborative problem solving are used after each cycle. The statistics using for data analysis are mean and percentage. In the research, it was found that: 5 students could reach the medium level of collaborative problem solving. Moreover, there is a student could reach the high level of collaborative problem solving. It showed that learning by using problem – based learning can develop the collaborative problem solving of students.